Gut microbiota derived metabolite trimethylamine N-oxide influences prostate cancer progression via the p38/HMOX1 pathway - Zhou, Yuhua; Lv, Jing; Jin, Shengkai; Fu, Chaowei; Liu, Bo; Shen, Yang; Li, Menglu; Zhang, Yuwei; Feng, Ninghan (Frontiers in Pharmacology, 2025)
BackgroundProstate cancer was the fourth most diagnosed cancer worldwide in 2022. Radical treatments and androgen deprivation therapy benefit newly diagnosed patients but impact quality of life, often leading to castration-resistant prostate cancer. Short-term dietary changes significantly affect the gut microbiota, which differs markedly between prostate cancer patients and healthy individuals, impacting both cancer progression and treatment response. A high-choline diet increases the risk of fatal prostate cancer, potentially mediated by the conversion of choline to the trimethylamine N-oxide (TMAO) by the gut microbiota.MethodsThe CCK8 assay was employed to investigate whether TMAO affects the proliferation ability of prostate cancer cells and to determine the appropriate drug concentration. Subsequently, CCK8 time gradients, colony formation assays, and EdU assays measured TMAO’s influence on cell proliferation. Wound healing and transwell migration assays evaluated TMAO’s effect on cell migration. RNA-seq analysis was performed to explore the mechanisms by which TMAO influences the proliferation and migration of prostate cancer cells. qPCR and Western blotting were utilized to validate the expression of related mRNA or proteins. Finally, we performed in vivo experiments to evaluate the effect of a high choline diet on the growth of subcutaneous tumors and lung metastases in mice.ResultsOur study found that TMAO enhances the proliferation and migration of prostate cancer cells by upregulating HMOX1 via activation of the MAPK signaling pathway, specifically p38 MAPK. In mouse subcutaneous tumor and lung metastatic tumor experiments, the high-choline diet increased prostate cancer cell proliferation and migration, resulting in significantly greater tumor volume and number of metastases than controls.ConclusionThis study is the first to demonstrate the role of the gut microbiota-derived metabolite TMAO in prostate cancer. TMAO promotes the proliferation and migration of prostate cancer cells by activating the p38 pathway and increasing HMOX1 expression. Reducing choline intake through dietary intervention may delay the onset and progression of prostate cancer, presenting significant clinical application value.